Designing an Automated Trading System Based on Oscar's Grind Money Management with Bollinger Bands and ADX for Trading XAU/USD on the MetaTrader 5 Platform - Bayu Sadewo; Haikal Rahman; Dedy Husrizal Syah (Economic: Journal Economic and Business, 2025)
This study designed and evaluated an automated trading system, or Expert Advisor (EA), for the XAU/USD instrument that integrates a trend-following strategy with a disciplined risk management approach. The system utilizes Bollinger Bands and the Average Directional Index for trading signals, and applies Oscar's Grind Money Management for position management. The EA's performance was tested on the MetaTrader 5 platform in two timeframe scenarios, H1 and H4, through backtesting over three years and real-time testing over one month. The findings consistently show that the strategy on the H4 timeframe significantly outperforms the H1 timeframe in both historical simulations and real-world testing, demonstrating higher stability, greater efficiency, and more controlled risk. Statistical tests also confirmed a significant difference in the final balance accumulation between the simulated and real-world environments. It was concluded that the use of the H4 timeframe proved highly effective for this strategy in filtering market noise and improving trading signal quality.